Multi-walled Carbon Nanotubes Reinforced-Based Magnesium Metal Matrix Composites Prepared by Powder Metallurgy. (September 2019) - Handayani, M; Ganta, M; Darsono, N; Sulistiyono, E; Lestari, F P.; Erryani, A; Astawa, I N G P; Lusiana; S Azhari, N
Abstract: Nanostructured carbons, for example, carbon nanotubes (CNTs) arise much attraction in the last decades because of its remarkable physical and mechanical properties. The unique physical, chemical and mechanical properties of CNTs make them attractive for biomedical applications. CNTs have been used to modify conventional biomedical materials to enhance mechanical properties, biocompatibility, or to impart other functionalities. One of the metal materials which attract high attention in the biomedical field for orthopaedics application is Magnesium. Recently, many researchers are studying the magnesium reinforced with a different kind of reinforcement. As a lightest metal structure material, magnesium matrix composites show many advantages over monolithic magnesium and magnesium alloys. In this study, Magnesium metal matrix was reinforced by multi-walled carbon nanotubes (MWCNTs) in order to observe the physical and the mechanical properties of the composites. The MWCNTs-Reinforced based magnesium MMC was performed using powder metallurgy process with MWCNTs loading are: 0, 0.1, 0.2, 0.3 and 0.5 %. The temperature of the sintering process was conducted at 600°C by flowing argon gas during the process with the holding time of 2 hours. The experiment result exhibited that the porosity of MMC was increased with the reinforcement by the increasing of the loading MWCNTs observed by metallography and SEM. The mechanical properties showed that the loading of MWCNTs 0.1 % increased the micro-hardness of MMC about 19% compared to pure magnesium, with the peaks at the loading of MWCNTs 0.3 % which increased the mechanical properties about 0.31% at highest hardness value of 46.5 HV.